Influence of exercise intensity and duration on perceived exertion in adolescent Taekwondo athletes - Haddad, M.; Chaouachi, A.; Wong, D. P.; Castagna, C.; Hue, O.; Impellizzeri, F.; Chamari, K. (European Journal of Sport Science, 2014)
The aim of this study was to examine the influence of exercise intensity and session duration on rating of perceived exertion (RPE) in adolescent Taekwondo (TKD) athletes. Twelve male youth competitive TKD athletes, aged between 13 and 18 years took part in this study. Training data (368 individual sessions) were collected during the 12 weeks of the pre-competitive TKD season. Daily training load was calculated using the heart rate and the session-RPE. Exercise intensity was also classified in five zones [i.e. 50-60%, 61-70%, 71-80%, 81-90% and 91-100% of maximal heart rate (HRmax)] and the time spent in each zone was expressed as percentage of total session time. The analysis of variance showed a significant main effect for zone (p<0.001) with most of the time (69%) spent at intensities between 61 and 90% of HRmax, and only 10% spent above 91% (mean differences compared to the other zones ranging from -6.6% versus zone 1 to -14.8% versus zone 3; p<0.0001). The individual correlation between session-RPE and HR-based methods were moderate to large. The stepwise multiple regression showed that RPE was influenced mainly by the time spent in the high intensity zone that explained 22.1% of the variance in RPE. Session duration accounted for only an additional 3.2%. The results suggest the time spent at high-intensity (i.e. between 91 and 100% HRmax) and only marginally the session duration influences the RPE referred to the whole training session. This seems to confirm that the determination of the TL multiplying the RPE and session duration is acceptable